Visuality in Academic Writing: Reading Textual Difference in the Work of Multilingual Student Writers - Zenger, Amy Alice (Journal of Academic Writing, 2016)
With the growth of the teaching of English globally and increasing numbers of students in English language medium universities, students in academic English classrooms can be expected to be literate in two or more languages. Multilingual writers in the university engage in high stakes academic writing even as they navigate differences among languages and academic writing systems. While research and pedagogies addressing the question of difference in the writing of multilingual students in English have focused primarily on verbal features, writing has come to be conceptualized in terms of multimodality. Writing is also a visual mode, and multilingual writers draw on their knowledge of different conventions and writing systems as they compose. To reflect on the visuality of writing, this article considers examples of textual difference in the English writing of multilingual university students in Lebanon. Multilingual approaches to teaching writing are developing quickly, but instruction in visual aspects of writing is still predominantly prescriptive. Instructors of academic writing have a responsibility to contextualize visual dimensions of academic writing, especially for multilingual writers. Qualitative studies will help understand the perceptions and experiences of multilingual academic writers as they negotiate all of the modes of writing, including the visual.